2006
DOI: 10.1007/s10658-006-9025-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential Inoculum Sources of Phaeomoniella chlamydospora in South African Grapevine Nurseries

Abstract: Petri disease of grapevine is primarily caused by Phaeomoniella chlamydospora. This pathogen affects mostly young grapevines, but is also implicated in esca disease of older grapevines. Little is known about the disease cycle of this fungus. Infected propagation material was identified as a major means of dissemination of the pathogen. Recently, the pathogen was also detected from soil in South Africa and airborne conidia have been found in vineyards. The aim of this study was to use a molecular detection tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 12 publications
(17 reference statements)
3
68
0
Order By: Relevance
“…PCR amplifications carried out from wood extract are being performed to detect Phaeomoniella chlamydospora (16,28,33), the other important pathogen associated with Petri disease (4). It has been used to detect this pathogen in rootstocks and grapevine propagation plants (30), and it has shown the potential sources of Phaeomoniella chlamydospora in plant nurseries (29). Sim- Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR amplifications carried out from wood extract are being performed to detect Phaeomoniella chlamydospora (16,28,33), the other important pathogen associated with Petri disease (4). It has been used to detect this pathogen in rootstocks and grapevine propagation plants (30), and it has shown the potential sources of Phaeomoniella chlamydospora in plant nurseries (29). Sim- Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Infection may take place in plant nurseries during the propagation process and storage (29,37). It may also happen because of the use of infected mother plants (10,12).…”
mentioning
confidence: 99%
“…Aroca et al (2010) found viable Phaeoacremonium spp., Phaeomoniella chlamydospora and Cadophoraluteoolivaceae propagules in pruning shears, grafting machines and peat used for callus formation. Likewise, Retief et al (2006) verified that the increase in the incidence of Phaeomoniella chlamydospora at the rooting site occurred due to contamination in the pre-storage hydration phase. Waite and Morton (2007) verified that contamination at this stage was derived from fungal structures from mother plants.…”
Section: Advances Observed In the Management Of New Diseasesmentioning
confidence: 60%
“…However, Gramaje and Di Marco (2015), in a survey conducted in 146 nurseries in Europe, pointed out that hydration was performed prior to cold storage, but that the hydration time was variable, from one hour to more than 24 hours. Different species of trunk fungi have been detected in this water, and contamination can come from the plant material that brings the inoculum from the field or by the poor hygiene of tanks (RETIEF et al, 2006;AROCA et al, 2010;AGUSTÍ-BRISACH et al, 2011;WAITE et al, 2013). Gramaje and Di Marco (2015) also observed that the use of chemicals in hydration varied among nurseries.…”
Section: Advances Observed In the Management Of New Diseasesmentioning
confidence: 99%
“…& Mugnai) Crous & W. Gams and Phaeoacremonium species that cause Petri disease (Halleen et al, 2003;Mostert et al, 2006a), as well as species within the Botryosphaeriaceae family that cause wood necrosis and dieback (Van Niekerk et al, 2004;. Propagation material taken from apparently healthy mother vines can already be infected by these pathogens prior to grafting (Fourie & Halleen, 2002;Halleen et al, 2003;Aroca et al, 2010) or become infected during the different nursery processes, mainly through the large number of wounds made (Halleen et al, 2003;Retief et al, 2006;Aroca et al, 2010;Gramaje & Armengol, 2011;Agustí-Brisach et al, 2013). Pleurostomophora richardsiae (Nannf.)…”
Section: Introductionmentioning
confidence: 99%